1997
DOI: 10.1242/dev.124.20.4153
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of the chick forebrain anlage by the prechordal plate

Abstract: We analysed the role of the prechordal plate in forebrain development of chick embryos in vivo. After transplantation to uncommitted ectoderm a prechordal plate induces an ectopic, dorsoventrally patterned, forebrain-like vesicle. Grafting laterally under the anterior neural plate causes ventralization of the lateral side of the forebrain, as indicated by a second expression domain of the homeobox gene NKX2.1. Such a lateral ventralization cannot be induced by the secreted factor Sonic Hedgehog alone, as this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(23 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…5a, b in Conklin [1932], von Kupffer [1894]; see also Lwoff [1894], Aasar [1931], Hill and Florian [1931], Adelmann [1932], De Lange [1936], Kopsch [1950]). Various authors have suggested that some mesodermal cells incorporate secondarily into the endodermal prechordal plate, implying a mixed endo-mesoderm or meso-endoderm [Adelmann, 1922[Adelmann, , 1926Seifert et al, 1993;Foley et al, 1997;Pera and Kessel, 1997;Nieuwkoop, 1999;Rowan et al, 1999]. However, in our opinion this point does not seem to be clearly established with appropriate labeling of mesodermal or endodermal elements.…”
Section: The Prechordal Hypothesismentioning
confidence: 68%
See 1 more Smart Citation
“…5a, b in Conklin [1932], von Kupffer [1894]; see also Lwoff [1894], Aasar [1931], Hill and Florian [1931], Adelmann [1932], De Lange [1936], Kopsch [1950]). Various authors have suggested that some mesodermal cells incorporate secondarily into the endodermal prechordal plate, implying a mixed endo-mesoderm or meso-endoderm [Adelmann, 1922[Adelmann, , 1926Seifert et al, 1993;Foley et al, 1997;Pera and Kessel, 1997;Nieuwkoop, 1999;Rowan et al, 1999]. However, in our opinion this point does not seem to be clearly established with appropriate labeling of mesodermal or endodermal elements.…”
Section: The Prechordal Hypothesismentioning
confidence: 68%
“…However, some of the originally epithelial endodermal prechordal plate cells do instead make an epithelio-mesenchymal transition, and become in situ free prechordal cells that migrate thereafter dorsalwards in front of the rostromedian acroterminal domain of the hypothalamus, reaching septo-preoptic roof plate levels [Schulte-Merker et al, 1994;Thisse et al, 1994;Bally-Cuif et al, 1995]. Modern studies have revealed several selective gene markers typical of the early (plate-like) and late (freely migrating) prechordal plate cells [Goosecoid, Crescent, Hex, Bmp7, Nodal, Shh, and FoxA2;Pera and Kessel, 1997;Dale et al, 1999;Lopez-Sanchez et al, 2005].…”
Section: The Prechordal Hypothesismentioning
confidence: 99%
“…The earliest chick hypothalamic progenitors are floor-plate-like cells, termed rostral diencephalic ventral midline (RDVM) cells, that express SHH , BMP7 , and NKX2–1 ( Figure 1A ) ( Dale et al, 1997 , 1999 ; Ohyama et al, 2005 ). RDVM cells are induced around Hamburger–Hamilton stage 8 (HH8) through the combined action of Sonic hedgehog (SHH), Nodal, and bone morphogenetic protein (BMP) signals from prechordal mesendoderm ( Dale et al, 1999 ; Manning et al, 2006 ; Ohyama et al, 2005 ; Patten et al, 2003 ; Pera and Kessel, 1997 ). Some RDVM cells later upregulate TBX2 , BMP2 , and FGF10 in response to BMP signals ( Figure 1A ) ( Manning et al, 2006 ) and generate tuberal and mammillary hypothalamic progenitors ( Fu et al, 2017 ; Manning et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Membranous organelles, including mitochondria, plasma membrane, and lysosomes, have been suggested to be the main sites of PDT damage. 3,4 Apoptosis after PDT has been demonstrated in vitro 5 and in vivo. 6 For this therapy, dyes such as hematoporphyrin derivatives are used.…”
Section: Introductionmentioning
confidence: 99%